Strength planning training software - Restrepo, J. E.; Ramos, J. E. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
This research work describes development software applied to strength training. This system allows the training plan (mesocycle, microcycle and sessions), structuring the distribution of training loads based in exercises derived of weightlifting, recognizing the athletes needs and the characteristics of the game in terms of physical requirements. The coach can display training load curves, control perform and check the progress of the process according to the objectives.